(untitled) (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Thummavonsa T, Musimun C, Watthana S, Muangsan N. 2025. Flowering, fruit set and breeding systems of Habenaria janellehayneana and H. rhodocheila in Phu Hin Rong Kla National Park, Thailand. Biodiversitas 26: 3246-3251. Reproductive biology studies are important information for orchids conservation in natural habitats, especially ones which have high potential for economic use. Over-collection is a main threat of orchid species with economic value. Moreover, the reduction of the habitat and climate change may result in population decline or extinction. Fruit set data is a preliminary evaluating the population survival, valuable for population conservation. This study aimed to examine flowering, natural fruit set and breeding systems of Habenaria janellehayneana and H. rhodocheila, attractive terrestrial orchids for pot plants, in Phu Hin Rong Kla National Park, Phitsanulok Province, Northern Thailand to collect basic information for in situ conservation. Two studied plots, 50x50 m plots of each species, were established to investigate the flowering and fruit set. Three experiments of hand-pollination, untouched, self- and cross-pollination were performed to compare with natural pollination to determine the breeding systems. Leaf length and shoot length showed no correlation with fruit set (r<0.5), while the number of flowers per inflorescence was slightly correlated (r=0.6). This result indicates that plant size is not a factor for fruit production, but the number of flowers per inflorescence is likely to be the factor to attract the pollinator. Natural fruit set is notably high in both species as they are nectar-rewarding species. Both species exhibited genetically self-incompatibility and non-autogamous but required pollinators for successful reproduction. Habenaria janellehayneana is firstly reported on its breeding system and fruit set, exhibiting as the main traits of the genus Habenaria. Moderately high number of fruit set in both species indicated that no pollinator scarcity. Maintaining the ecosystem of their habitat is necessary for conserve these orchid populations.